2019
DOI: 10.1016/j.apergo.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic versus monoscopic displays: Learning fine manual dexterity skills using a microsurgical task simulator

Abstract: Easier initial learning process when using a stereoscopic display.• Funnel-shaped task simulator for fine manual dexterity in a microsurgical context.• Recording and analysis of learning curves extended to a plateau of best performance.• Linear and non-linear mixed effects models to consider subject specific inferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Additionally, according to the cognitive load theory, more mental connections are activated during stereoscopic viewing that could possibly support the memorization process [21]. Stereoscopic imaging systems have also proven to demonstrate a significant improvement in the acquisition of minimally invasive surgical skills for novice surgeons as compared to the standard 2D imaging system [22][23][24]. For instance, in a study by Schoenthaler et al utilizing a surgical simulator model for laparoscopic surgery, stereoscopic imaging led to an improvement while performing the laparoscopic phantom tasks [22].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, according to the cognitive load theory, more mental connections are activated during stereoscopic viewing that could possibly support the memorization process [21]. Stereoscopic imaging systems have also proven to demonstrate a significant improvement in the acquisition of minimally invasive surgical skills for novice surgeons as compared to the standard 2D imaging system [22][23][24]. For instance, in a study by Schoenthaler et al utilizing a surgical simulator model for laparoscopic surgery, stereoscopic imaging led to an improvement while performing the laparoscopic phantom tasks [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that microsurgical performance under two-dimensional visualization is possible but requires more time and may be not so effective, compared with a three-dimensional visualization. 35,36 Because two-dimensional visualization of a smartphone resembles the view obtained during laparoscopic procedures, several investigators have encouraged its use as an image source for training in laparoscopic skills. 37,38 There are previous reports of using smartphones as magnification devices for microsurgical training.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that microsurgical performance under two-dimensional visualization is possible but requires more time and may be not so effective, compared with a three-dimensional visualization. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Aside from manual dexterity 13 , 14 , the learning experience 15 and visual-spatial ability appear to play crucial roles in the acquisition of surgical skills 16 , 17 . The learning experience results from the totality of influences that affect the trainee during the learning process, such as individualization and the quality of the application or the stimulation of memorization 18 .…”
Section: Introductionmentioning
confidence: 99%